Mental health in workplace: the role of safety and health committee - Ismail, Fadillah; Ahmad, Nurul Ameera; Abdul Kadir, Adibah; Mustafa, Siti Aisyah; Atan @ Yaakub, Siti Anisah (Penerbit UTHM, 2020)
Safety and Health Committee services has been established since 1 January 1997 in Malaysia. According to Section 30 of Occupational Safety and Health Act (OSHA) 1994, safety and health committee need to be establish and it is compulsory to the employers who have more than 40 employees. Department of Safety and Health (DOSH) are capable to issue an improvement or prohibition notice in order to get improvement in future.